2006
DOI: 10.4319/lo.2006.51.1_part_2.0763
|View full text |Cite
|
Sign up to set email alerts
|

Is phosphorus retention in autochthonous lake sediments controlled by oxygen or phosphorus?

Abstract: Eutrophication of various lakes on the Swiss Plateau was targeted in the 1980s by reducing external nutrient loading and installing aeration/oxygenation systems. For five eutrophic lakes, three of which have been artificially oxygenated and aerated for almost 20 yr, phosphorus (P) balances were established using input, water-column inventory, export via the outlet, and sediment core data. To separate the effects of aeration/oxygenation from the effects of P-input reduction, two measures of P retention were det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(45 citation statements)
references
References 30 publications
4
41
0
Order By: Relevance
“…The only efficient long-term measure to reduce summer anoxia and reestablish lake ecosystems is the reduction of anthropogenic nutrient loads or external organic loadings. A similar conclusion was found by Liboriussen et al (2009) regarding oxygenation to prevent anoxia and concurrent hypolimnetic NH z 4 accumulation, by Moosmann et al (2006) and Gä chter and Wehrli (1998) regarding oxygenation and artificial mixing to reduce lakeinternal P loading, by Annadotter et al (1999) regarding sediment dredging to reduce lake-internal P loading, and by Mü ller and Stadelmann (2004) regarding oxygenation and artificial mixing to improve conditions for egg survival of bottom-spawning fish. Nevertheless, the previously mentioned lake management measures can provide temporary relief from negative effects of anoxia.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…The only efficient long-term measure to reduce summer anoxia and reestablish lake ecosystems is the reduction of anthropogenic nutrient loads or external organic loadings. A similar conclusion was found by Liboriussen et al (2009) regarding oxygenation to prevent anoxia and concurrent hypolimnetic NH z 4 accumulation, by Moosmann et al (2006) and Gä chter and Wehrli (1998) regarding oxygenation and artificial mixing to reduce lakeinternal P loading, by Annadotter et al (1999) regarding sediment dredging to reduce lake-internal P loading, and by Mü ller and Stadelmann (2004) regarding oxygenation and artificial mixing to improve conditions for egg survival of bottom-spawning fish. Nevertheless, the previously mentioned lake management measures can provide temporary relief from negative effects of anoxia.…”
Section: Discussionmentioning
confidence: 50%
“…Low hypolimnetic DO can in turn have a serious effect on biological processes, either via direct toxicity on fish and bottom organisms (Kalff 2002) or indirectly via toxic by-products of anaerobic mineralization (Wang and Chapman 1999). Moreover, it has been shown that hypolimnetic anoxia can enhance the sediment release of soluble reactive phosphorus (P; Larsen et al 1981;Hupfer and Lewandowski 2008), although the DO concentration at the sediment-water interface is not the only controlling factor (Moosmann et al 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings suggest that the content of OP in sediments is lower than that of IP, which primarily consists of Ca-P (apatitic phosphorus) in sediments from calcareous regions [19]. This is probably due to the typical carbonate-rock dissolution environment of the lake, where there is abundant calcium because deposition of phosphorus is limited by the binding capacity of the sediment [31]. Phosphorus in water is integrated into particles by biological absorption (primary production), chemical transfer (adsorption and sedimentation) and other processes, and the particles sink continually.…”
Section: Determination Of Phosphorus Forms In Sediments From the Lakementioning
confidence: 63%
“…Organic P originates from settled organic material which is refractory or not yet mineralised by microorganisms. Inorganic phases include P sorbed onto the surface of iron(oxy)hydroxides, aluminium hydroxides, clays and calcite (Moosmann et al, 2006). P associated with Fe(III) minerals have been found in anoxic marine and estuarine sediments, indicating a resistance towards reductive dissolution of these compounds, at least under nonsulfidic conditions (Hyacinthe and Van Cappellen, 2004;Lehtoranta et al, 2009).…”
Section: Introductionmentioning
confidence: 99%